Customer Satisfaction towards Public Service Delivery at Hospital Sultan Abdul Halim, Sungai Petani, Kedah / Norasheda Abdul Wahab and Nur Fazidah Mohd Razi - Abdul Wahab, Norasheda; Mohd Razi, Nur Fazidah (2010)
Many health organizations are currently moving to offer their service effectively to the customers. However, providing excellent services to the customers is not an easy task since service delivery in the hospital may require a dynamic composition of a number of elementary services in an organization. This study empirically examines the factors of customer satisfaction towards healthcare public service delivery from the perspective of consultation, accessibility, courtesy, information and redress (remedy failures). This research is conducted in order to investigate customer satisfaction in Hospital Sultan Abdul Halim, Kedah and a questionnaire was distributed to the customers that received health services. Hence, this research will lead to initiatives to enhance public service delivery to provide the best quality of service that is faster, better and more flexible services to the customers